In Vitro Production Of Goat Embryos In Bangladesh (Bangladesh Journal of Animal Science, 2012)
The present study was undertaken to collect the quality cumulus-oocyte-complexes (COCs) from ovaries of goat from slaughterhouse by aspiration to establish the suitable culture condition for in vitro maturation (IVM), in vitro fertilization (IVF) and in vitro culture (IVC). Follicular COCs were collected from follicles of 2-6 mm diameter, categorized by microscopic observation and cultured for 22 h in TCM-199 medium supplemented with 5% fetal calf serum (FCS) to determine the success rate of in vitro maturation in a condition of 5% CO2 in air at 38.5°C. The collected ovaries were classified as type-I (corpus luteum absent) and type-II (corpus luteum present). The average numbers of follicles aspirated per ovary were 3.15 and 2.57 in type-I and type-II, respectively. The collected COCs were classified into normal COCs (grade A and B) and abnormal COCs (grade C and D). The number of normal and abnormal COCs collected from two type of ovaries were significantly (P